LOW BACK PAIN PADA TENAGA KESEHATAN DI RUANG OPERASI: SEBUAH TINJAUAN LITERATUR - Poppy Monika Sari; Winda Trijayanthi Utama (Medula, 2026)
Low Back Pain is one of the most common musculoskeletal complaints among Healthcare Workers, especially nurses, and directly affects quality of life, work performance, and productivity. The high physical demands of healthcare services increase the risk of Low Back Pain through multiple factors. Individual factors include age, body mass index, level of physical activity, and a history of back injury. Occupational factors involve non-ergonomic working postures, patient lifting and transfer activities, repetitive movements, prolonged working hours, and heavy workloads. This study aims to review the literature related to risk factors, impacts, and the effectiveness of preventive interventions for Low Back Pain among Healthcare Workers. The method used is a literature review of scientific articles retrieved from relevant international databases, focusing on Healthcare Workers as the primary population. The review results show that more than half of Healthcare Workers in various countries report experiencing Low Back Pain, with occupational factors identified as the main contributors. Reported impacts include increased absenteeism, decreased work performance, and a higher risk of developing chronic musculoskeletal disorders. Preventive interventions such as workplace ergonomic modifications and posture education demonstrate more consistent effectiveness in reducing the incidence of Low Back Pain compared to physical activity-based interventions or stretching exercises alone. Stretching exercises provide limited benefits when not combined with ergonomic improvements. Therefore, prevention of Low Back Pain among Healthcare Workers requires an integrated approach that combines education, application of ergonomic principles, and systematic workload management to reduce prevalence and mitigate its negative impact.